2008
DOI: 10.1677/erc.1.1315
|View full text |Cite
|
Sign up to set email alerts
|

Mitotane increases the radiotherapy inhibitory effect and induces G2-arrest in combined treatment on both H295R and SW13 adrenocortical cell lines

Abstract: Mitotane, 1,1-dichloro-2-(o-chlorophenyl)-2-(p-chlorophenyl)ethane (o,p 0 -DDD) is an agent with adrenotoxic effect, which is able to block cortisol synthesis. This drug and radiotherapy are used also in adrenal cancer treatment even if their biological action in this neoplasia remains unknown. We investigated the effects of o,p 0 -DDD and ionizing radiations (IR) on cell growth inhibition and cell cycle perturbation in H295R and SW13 adrenocortical cancer cells. Both cell lines were irradiated at a 6 Gy dose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
38
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 38 publications
7
38
0
Order By: Relevance
“…However, this effect on cell proliferation was not paralleled by a significant influence on apoptosis and cell cycle in mitotane-sensitive H295R cells. This observation, already presented in previous reports detailing the effects of mitotane on cell cycle used as a single agent (Cerquetti et al, 2008), supports a cytostatic rather than cytotoxic effect of mitotane in ACC cells.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…However, this effect on cell proliferation was not paralleled by a significant influence on apoptosis and cell cycle in mitotane-sensitive H295R cells. This observation, already presented in previous reports detailing the effects of mitotane on cell cycle used as a single agent (Cerquetti et al, 2008), supports a cytostatic rather than cytotoxic effect of mitotane in ACC cells.…”
Section: Discussionsupporting
confidence: 85%
“…Second, the anti-neoplastic properties of mitotane seem to be adrenocortical-specific, since mitotane does not appear to be effective on other tumor cells lines, such as those of lung origin (Volante et al, 2012). Moreover, the mechanisms underlying its adrenocortical-specific anti-neoplastic properties are largely unknown and possibly related to different biological processes (including energetic metabolism, stress response and other cellular functions), as suggested by proteomic analysis of H295R cells (Stigliano et al, 2008). Finally, the possible interactions of mitotane with other antitumor agents, including the chemotherapeutic drugs commonly used for ACC treatment, are poorly explored.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CCNB/ CDC2 complex was found to be overexpressed in Endocrine-Related Cancer (2009) 16 895-906 www.endocrinology-journals.org several malignancies (Egloff et al 2006); however, its exact role in ACC is unclear. Treatment of ACC cell lines either with 17b-estradiol (E 2 ) and progesterone (Brown et al 2008) or with the adrenolytic compound mitotane combined with irradiation therapy (Cerquetti et al 2008) induced G2/M block and apoptosis. Progesterone alone and in combination with E 2 induced mitotic perturbations in SW-13 cells via decreased CCNB1 and CCND1 expression (Brown et al 2008).…”
Section: Z Tömbö L Et Al: Micrornas In Adrenocortical Tumorsmentioning
confidence: 99%
“…On the other hand, Dan and Yamori [15] suggested that changes in the level of cyclin B1 and G2/M arrest in A549 cells exposed to doxorubicin are regulated in the manner independent of p53, because similar changes were not induced by cisplatin, a well-known p53 activator [15]. In agreement with that, it was shown that an increased level of cyclin B1 may appear in some G2/M-arrested cancer cells with defects in p53 [16]. However, we could not exclude that the increase in the cyclin level observed by us may be strictly correlated with morphological changes appearing in this population of cells after treatment with doxorubicin.…”
Section: Discussionmentioning
confidence: 67%